Some Properties of Solutions for the Sixth-Order Cahn-Hilliard-Type Equation - Zhao Wang; Changchun Liu (Abstract and Applied Analysis)
We study the initial boundary value problem for a sixth-order Cahn-Hilliard-type equation which describes the separation properties of oil-water mixtures, when a substance enforcing the mixing of the phases is added. We show that the solutions might not be classical globally. In other words, in some cases, the classical solutions exist globally, while in some other cases, such solutions blow up at a finite time. We also discuss the existence of global attractor.